Traditional healer support to improve HIV viral suppression in rural Uganda (Omuyambi): study protocol for a cluster randomized hybrid efectiveness-implementation trial - Sundararajan, Radhika; Hooda, Misha; Lai, Yifan; Nansera, Denis; Audet, Carolyn; Downs, Jennifer; Lee, Myung Hee; McNairy, Margaret; Muyindike, Winnie; Mwanga-Amumpaire, Juliet (BioMed Central Ltd, 2024)
Rural African people living with HIV face significant challenges in entering and remaining in HIV care. In rural Uganda, for example, there is a threefold higher prevalence of HIV compared to the national average and lower engagement throughout the HIV continuum of care. There is an urgent need for appropriate interventions to improve entry and retention in HIV care for rural Ugandans with HIV. Though many adults living with HIV in rural areas prioritize seeking care services from traditional healers over formal clinical services, healers have not been integrated into HIV care programs. The Omuyambi trial is investigating the effectiveness of psychosocial support delivered by traditional healers as an adjunct to standard HIV care versus standard clinic-based HIV care alone. Additionally, we are evaluating the implementation process and outcomes, following the Consolidated Framework for Implementation Research.BACKGROUNDRural African people living with HIV face significant challenges in entering and remaining in HIV care. In rural Uganda, for example, there is a threefold higher prevalence of HIV compared to the national average and lower engagement throughout the HIV continuum of care. There is an urgent need for appropriate interventions to improve entry and retention in HIV care for rural Ugandans with HIV. Though many adults living with HIV in rural areas prioritize seeking care services from traditional healers over formal clinical services, healers have not been integrated into HIV care programs. The Omuyambi trial is investigating the effectiveness of psychosocial support delivered by traditional healers as an adjunct to standard HIV care versus standard clinic-based HIV care alone. Additionally, we are evaluating the implementation process and outcomes, following the Consolidated Framework for Implementation Research.This cluster randomized hybrid type 1 effectiveness-implementation trial will be conducted among 44 traditional healers in two districts of southwestern Uganda. Healers were randomized 1:1 into study arms, where healers in the intervention arm will provide 12 months of psychosocial support to adults with unsuppressed HIV viral loads receiving care at their practices. A total of 650 adults with unsuppressed HIV viral loads will be recruited from healer clusters in the Mbarara and Rwampara districts. The primary study outcome is HIV viral load measured at 12 months after enrollment, which will be analyzed by intention-to-treat. Secondary clinical outcome measures include (re)initiation of HIV care, antiretroviral therapy adherence, and retention in care. The implementation outcomes of adoption, fidelity, appropriateness, and acceptability will be evaluated through key informant interviews and structured surveys at baseline, 3, 9, 12, and 24 months. Sustainability will be measured through HIV viral load measurements at 24 months following enrollment.METHODSThis cluster randomized hybrid type 1 effectiveness-implementation trial will be conducted among 44 traditional healers in two districts of southwestern Uganda. Healers were randomized 1:1 into study arms, where healers in the intervention arm will provide 12 months of psychosocial support to adults with unsuppressed HIV viral loads receiving care at their practices. A total of 650 adults with unsuppressed HIV viral loads will be recruited from healer clusters in the Mbarara and Rwampara districts. The primary study outcome is HIV viral load measured at 12 months after enrollment, which will be analyzed by intention-to-treat. Secondary clinical outcome measures include (re)initiation of HIV care, antiretroviral therapy adherence, and retention in care. The implementation outcomes of adoption, fidelity, appropriateness, and acceptability will be evaluated through key informant interviews and structured surveys at baseline, 3, 9, 12, and 24 months. Sustainability will be measured through HIV viral load measurements at 24 months following enrollment.The Omuyambi trial is evaluating an approach that could improve HIV outcomes by incorporating previously overlooked community lay supporters into the HIV cascade of care. These findings could provide effectiveness and implementation evidence to guide the development of policies and programs aimed at improving HIV outcomes in rural Uganda and other countries where healers play an essential role in community health.DISCUSSIONThe Omuyambi trial is evaluating an approach that could improve HIV outcomes by incorporating previously overlooked community lay supporters into the HIV cascade of care. These findings could provide effectiveness and implementation evidence to guide the development of policies and programs aimed at improving HIV outcomes in rural Uganda and other countries where healers play an essential role in community health.ClinicalTrials.gov NCT05943548. Registered on July 5, 2023. The current protocol version is 4.0 (September 29, 2023).TRIAL REGISTRATIONClinicalTrials.gov NCT05943548. Registered on July 5, 2023. The current protocol version is 4.0 (September 29, 2023). MEDLINE - Academic